An expert system for predicting aeration performance of weirs by using ANFIS - Baylar, Ahmet; Hanbay, Davut; Ozpolat, Emrah (Pergamon-Elsevier Science Ltd, 2008)
A free overfall jet from a weir plunging into downstream water causes entrainment of the air bubbles if the free overfall jet velocity exceeds a certain critical value and hence aeration occurs. This study investigates the free overfall jets from triangular sharp-crested weirs and effect on their air entrainment rate and the aeration efficiency. An expert system based on adaptive network based fuzzy inference system (ANFIS) was obtained for predicting air entrainment rate and aeration efficiency of weirs. The performance of ANFIS model was compared with multi nonlinear and linear regression models. There were good agreements between the measured values and the values obtained using the ANFIS model. (C) 2007 Elsevier Ltd. All rights reserved.
Keywords: ANFIS; aeration efficiency; air entrainment rate; weir